Politische Soziologie: Versuch einer Neubestimmung - Schuppert, Gunnar Folke (Nomos Verlagsgesellschaft mbH & Co. KG, 2026)
This book is an attempt not only to update the discipline of political sociology—which has become somewhat marginalized—but also to give it clear contours from a perspective specific to the sociology of domination. It focuses on presenting six subfields of sociology that are particularly relevant to power and specifically incorporates recent developments and questions. This applies, for example, to the observable shift from rule-based to purely power-based conceptions of order, as well as to the need to develop a sociology of rule-breakers and lawbreakers.